Relationship of hearing loss with absenteeism at the MOLICAL S.A.C Planta – 2017 - Gonzales Ortiz, Esteve Alan (2021)
The main objective of this research is to determine if there is a relationship between hearing loss and absenteeism from work. This research used as a methodology the type of observational, descriptive, cross-sectional, retrospective research. According to the depth, it is a correlational study. The study population comprised 100% of workers at the MOLICAL S.A.C plant, which corresponded to 87 workers. After the statistical analysis, it was determined that the observed significance value is p = 0.004, so we see it is higher than 7.815, consequently, the null hypothesis is discarded and the research hypothesis is admitted, because evidence is found necessary to affirm that there is a relationship, which allows us to agree that hearing loss affects absenteeism of workers (Rojas Concha, 2014). These research results indicate that sufficient evidence is presented to accept the statement that there is a relationship between hearing loss and absenteeism from work at the MOLICAL S.A.C Plant, since 66.1% of the plant workers are negatively affected by hearing loss, it was also possible to show that of the total number of workers who suffered a health problem during the year 2017, 21.8% of workers presented health problems. Auditory type. Likewise, it was established that the high rate of absenteeism negatively affects 72.5% the activities carried out in the aforementioned company. For these reasons, in the MOLICAL S.A.C production plant and other similar plants, it would be extremely important to implement preventive measures related to the impact of occupational hearing loss and the monitoring of justified and unjustified absences.